The effect of glutamine supplement on small intestinal morphology and xylose absorptive ability of weaned piglets - C. B. Hsu; H. J. Huang; C. H. Wang; H. T. Yen; B. Yu (African Journal of Pig Farming, 2015)
The purpose of this study is to demonstrate the effects of glutamine (Gln) supplement on small intestinal morphology, xylose absorptive and growth performance of weaned piglets. Forty eight piglets weaned at 28 ± 2 days of age were randomly allotted to three treatment groups. A basal corn-soybean diet was formulated to contain 20.3% protein and 3450 kcal DE/kg diet. Glutamine was supplemented to the basal diet at 0% (control), 1% (Gln 1%) and 2% (Gln 2%). Pigs were fed experimental diets for three weeks. The results showed that the villous height of the Gln groups tended higher than the control group in duodenum and jejunum (P < 0.1). Glutamine supplementation increased plasma net xylose absorptive concentration from 0.78 to 1.20 and 0.95 to 1.23 in Gln 1% and Gln 2% group, respectively, which were better than the control group (0.86 to 0.97) in day 7 to 14 after weaning. Growth performance was not significantly affected by Gln supplement; however, average daily gain was approximately improved from 21 to 28% by Gln supplement compared to the control group during 21 days of experimental period. In summary, the results suggested that dietary supplementation of Gln could be beneficial in small intestinal villous morphology and xylose absorptive capacity, and could have a slight contribution to the average daily gain of weaned piglets.